CONTRIBUTION OF B. O. ORUZBAEVA TO KYRGYZ TERMINOLOGY AND TERMS IN LINGUISTICS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the contribution of academician Bubuina Omurzakovna Oruzboeva to Kyrgyz terminology, the place and significance of her works among Kyrgyz linguists. Language as a social phenomenon develops as society develops. The article linguistically analyzes Kyrgyz and Uzbek riddles borrowed from Turkic languages, and provides linguistic features of the riddle genre and its terms.
Keywords: term, terminology, anagram, logoryph, metagram, acrory, sharada, crossword, rebus, cryptogram, enigma, logical puzzles